PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP HASIL BELAJAR SISWA KELAS X SMA ISLAM BAWARI PONTIANAK - Rifanza, Syalas; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the significant effect of the professional competencies of sociology teachers on student learning outcomes in class X. The method used was a quantitative method using inferential statistics correlation studies. The population in this study were all students of class X Islam Bawari High School Pontianak amounting to 98. From the total population taken 79 respondents, the sampling technique was simple random sampling. Data collection techniques used in this study are indirect communication techniques with data collection tools, namely questionnaires. Data were analyzed using descriptive analysis of achievement of scores on each variable and inferential analysis. The results of the study show that tcount of 2.954 shows that there is an influence of the independent variable (X) on the dependent variable (Y). When compared with t table of 1,664, t count is greater than t table or 2,954> 1,664 so Ha is accepted and Ho is rejected. This means that there is a significant influence between the professional competencies of sociology teachers on the learning outcomes of class X Islam Bawari High School Pontianak. After testing the hypothesis, the coefficient of determination is 21.3%, which means that the professional competence of sociology teachers has an effect of 21.3% on the learning outcomes of class X students of Islam Bawari High School Pontianak with a low level of relationship. While the rest which is equal to 78.7% is influenced by other variables not examined by researchers.Â Keywords:Â Professional Competence, Student Learning Outcomes, Sociology TeachersÂ